(untitled) (Research, Society and Development, 2020)
Bullying is the practice of violating human rights that embarrasses and inferiorizes its victims. Half of the world’s children and youth have already suffered some form of bullying. In Brazil, about 43% of the population of students experiences threats, oppression, intimidation, humiliation and mistreatment. The objective of the research is the perception of Basic Education students regarding bullying. The study is quantitative and of a descriptive nature, using the Statistical Package for the Social Sciences - SPSS software for the analysis of the collected data. 271 students participated in this research, being from two public schools and a private one from the State of Mato Grosso. It was identified that approximately 25% and 55% of students from public and private schools, respectively, suffered some violation of their rights in the school environment. Among the assaults stand out nicknames, insults for the physical characteristics and the physical assaults. It is concluded that such data confirm the emergence of awareness and violence prevention actions and show the need to include these actions in the schools curriculum.